Characterizations of Highly Expressed Genes of Four Fast-Growing Bacteria - Karlin, Samuel (American Society for Microbiology, 2001)
Predicted highly expressed (PHX) genes are characterized for the completely sequenced genomes of the four fast-growing bacteria Escherichia coli, Haemophilus influenzae, Vibrio cholerae, and Bacillus subtilis. Our approach to ascertaining gene expression levels relates to codon usage differences among certain gene classes: the collection of all genes (average gene), the ensemble of ribosomal protein genes, major translation/transcription processing factors, and genes for polypeptides of chaperone/degradation complexes. A gene is predicted highly expressed (PHX) if its codon frequencies are close to those of the ribosomal proteins, major translation/transcription processing factor, and chaperone/degradation standards but strongly deviant from the average gene codon frequencies. PHX genes identified by their codon usage frequencies among prokaryotic genomes commonly include those for ribosomal proteins, major transcription/translation processing factors (several occurring in multiple copies), and major chaperone/degradation proteins. Also PHX genes generally include those encoding enzymes of essential energy metabolism pathways of glycolysis, pyruvate oxidation, and respiration (aerobic and anaerobic), genes of fatty acid biosynthesis, and the principal genes of amino acid and nucleotide biosyntheses. Gene classes generally not PHX include most repair protein genes, virtually all vitamin biosynthesis genes, genes of two-component sensor systems, most regulatory genes, and most genes expressed in stationary phase or during starvation. Members of the set of PHX aminoacyl-tRNA synthetase genes contrast sharply between genomes. There are also subtle differences among the PHX energy metabolism genes between E. coli and B. subtilis, particularly with respect to genes of the tricarboxylic acid cycle. The good agreement of PHX genes of E. coli and B. subtilis with high protein abundances, as assessed by two-dimensional gel determination, is verified. Relationships of PHX genes with stoichiometry, multifunctionality, and operon structures are also examined. The spatial distribution of PHX genes within each genome reveals clusters and significantly long regions without PHX genes.